Optical chemical sensors and biosensors for food safety and security applications - Narayanaswamy, Ramaier (Acta Biologica Szegediensis, 2006)
Over the past two decades or so, the incorporation of optical techniques in the development of chemical sensors and biosensors have been investigated resulting in novel and very interesting devices with great promise for many areas of applications. These are truly integrated and interdisciplinary systems that invoke expertise from the fields of chemistry, biochemistry, physics and electronics. Optical chemical sensors and biosensors utilise immobilised reagents and novel materials that can result in a variety of optode designs that are suitable for a variety of measurements in environmental, biomedical, industrial and process control areas.